E-commerce development and entrepreneurship in the People's Republic of China - Bihong Huang; Mohamed Shaban; Quanyun Song; Yu Wu (Asian Development Bank Institute (ADBI), 2018)
In this paper, we utilize an e-commerce development indicator in tandem with big data to measure the variations of e-commerce development across counties in the People's Republic of China and assess its impact on entrepreneurship in both rural and urban areas. We find that households living in counties with higher levels of e-commerce development are more likely to run their own businesses. Further study indicates that e-commerce development not only significantly increases the entry of new startups but also decreases the exit of incumbent businesses. Moreover, we find that e-commerce development induces sectoral change of household entrepreneurship. It promotes the entrepreneurship in the manufacturing and wholesale sectors, but reduces the entrepreneurship in the retail, hotel, and catering sectors. In addition, we show that e-commerce prosperity fuels entrepreneurship by alleviating the financial constraints and moderates the reliance of household entrepreneurship on social networks.
Keywords: L81; 330; e-commerce development; big data; entrepreneurship